Management of a Diabetic Patient with Philosophical Mental Attitude: A Case Report - Debarchita Sarangi (Institute of Medico-legal Publications Pvt Ltd, 2020)
Diabetes Mellitus is a metabolic disorder. It has been recognized as a pandemic and is a nutritional disorder.It affects almost every organ system in the human body, including the patient’s psychology. It occurs due toirregularity in the insulin secretion. The most characteristic feature is hyperglycemia. The underlying factors,contributing to this disease are age,genetics, obesity, lack of physical activity, etc. A prosthodontist shouldhave a thorough understanding of the general considerations for diabetes mellitus patients as well as theprosthodontic consideration. This article reviews the prosthodontic management of a patient with diabetesmellitus, supported by a case report of a complete denture patient with a philosophical mental attitude.